Alterações nos teores de macronutrientes em plantas de feijoeiro infectadas por Curtobacterium flaccumfaciens pv. flaccumfaciens - Maringoni, Antonio Carlos [UNESP] (Universidade Federal de Lavras (UFLA), 2003)
The objective of this research was to evaluate nitrogen, phosforus, potassium, calcium, magnesium, and sulfur contents on shoot dry matter of bean plants cultivars IAC Carioca Arua, IAC Carioca Pyata, IAC Carioca Akyta (resistant to the bacterial wilt), IAC Carioca, and Perola (susceptible to the bacterial wilt) inoculated or not with one isolate of Curtobacterium flaccumfaciens pv. flaccumfaciens. It was observed that all cultivars infected by C. flaccumfaciens pv. flaccumfaciens showed reduction of shoot dry matter and macronutrient contents. However, resistant cultivars had a lower reduction of nitrogen, phosforus, potassium, calcium, and magnesium contents than bacterial wilt suceptible cultivars.
Macronutrients content alterations in dry bean plants infected by Curtobacterium faccumfaciens pv. flaccumfaciens
Keywords: Phaseolus vulgaris; disease; nutrient content; bacterial wilt